Pengelolaan Instagram Humas @Diskominfojambi Dalam Memenuhi Informasi Publik - Gusnita, Aulia; Darwis, Yuliandre (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2024)
Social media is the term for the use of online technology to share opinions, discuss and communicate through online technology. One of the most popular social networks today is Instagram. Instagram management is a management strategy aimed at achieving predetermined goals, objectives and functions. The aim of the research is to find out how to consider choosing Instagram as a publication medium for Diskominfo Jambi, to find out how the Instagram Public Relations of Diskominfo Jambi is managed to meet the information needs of the community and to find out where the obstacles are and how to overcome the obstacles that exist in the process of managing Instagram Diskominfo Jambi. This research uses qualitative methods with descriptive research type. The concept used in this research is the circular model SoMe for social communication which includes sharing, optimization, management, involvement to create efficient management and no waste of energy. The search results at the Instagram sharing stage were chosen because of its popularity and the millennial generation is considered to gather a lot on the Instagram social network. Optimization is carried out by maximizing the use of Instagram features even though they still seem minimal so that captions and hashtags are less than optimal. At the management stage, it seems there is no public relations supervision to monitor Instagram's growth, making Instagram @diskominfojambi look monotonous and less interactive. And at the Engage stage, this can only be achieved through collaboration with influencers and no research has been carried out on the audience, especially @diskominfojambi followers.